Performance of PM compacted Cu-TaC electrodes during EDM - Mohammed, Baba Ndaliman; Khan, Ahsan Ali; Mohd. Zain, Zakaria (IIUM, 2011)

(untitled)
Electrical Discharge Machining (EDM) has been used in recent years to modify surfaces of the work materials to achieve additional properties in terms of hardness, wear resistance etc. This paper reports the investigations carried out using powder metallurgy (PM) compacted Cu-TaC electrodes to possibly achieve the surface modification. The main electrode and machining parameters used during the investigation were electrode’s compositions, compacting pressures and the discharge currents. The electrodes in green form were produced from two different compositions (30 and 55% of TaC) and compacted at two different pressures of 1,500 and 3,000 psi. These were used to machine mild steel material at the discharge current range of 2.5 to 6.5A. The outputs investigated were the Tool Wear Rate (TWR), Material Removal Rate (MRR), and Surface Roughness (SR) of the machined surface. Results showed that the tool electrode wears are generally low at low peak currents and high percentage of TaC compositions, with net material depositions on the work surface. The net MRR are high at higher currents, lower compositions of TaC and higher compacting pressures. The best surface finishes were obtained at lower currents.